2020
DOI: 10.1186/s12872-020-01443-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating metabolite profiles to predict response to cardiac resynchronization therapy

Abstract: Background: Heart failure is associated with ventricular dyssynchrony and energetic inefficiency, which can be alleviated by cardiac resynchronization therapy (CRT) with approximately one-third of non-response rate. Thus far, there is no specific biomarker to predict the response to CRT in patients with heart failure. In this study, we assessed the role of the blood metabolomic profile in predicting the response to CRT. Methods: A total of 105 dilated cardiomyopathy patients with severe heart failure who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, there are 14 specific metabolites in IDCM, dominated by amino acids (e.g., isoleucine, leucine, ureidosuccinic acid and pyroglutamic acid), carbohydrates (e.g., erythrose and ribitol) and fatty acids (e.g., 2-methylglutaric acid and azelaic acid). Gong et al [ 53 ] performed a study of serum metabolomic analysis to predict response to cardiac resynchronisation therapy in patients with IDCM. They found that isoleucine and linoleic acid were potential biomarkers in distinguishing responders from non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are 14 specific metabolites in IDCM, dominated by amino acids (e.g., isoleucine, leucine, ureidosuccinic acid and pyroglutamic acid), carbohydrates (e.g., erythrose and ribitol) and fatty acids (e.g., 2-methylglutaric acid and azelaic acid). Gong et al [ 53 ] performed a study of serum metabolomic analysis to predict response to cardiac resynchronisation therapy in patients with IDCM. They found that isoleucine and linoleic acid were potential biomarkers in distinguishing responders from non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a cross-validation analysis also showed a satisfactory and robust performance of the model with AUC of 0.910 in training dataset and 0.880 in the testing dataset, demonstrating potential metabolite markers for predicting HF response to CRT treatment [40]. Another study was conducted by Gong et al [41] using an ultra-performance liquid chromatography quadrupole-time-of-flight mass spectrometry (UPLC-qTOF-MS) for comprehensive serum metabolomics analyses to help predict response to CRT. In their study, a discovery set of 27 responders versus 24 nonresponders and a validation set of 36 responders and 18 nonresponders were investigated and they reported increased concentrations of isoleucine and linoleic acid and a decreased concentration of tryptophan in response to CRT relative to nonresponders.…”
Section: Biomarkers Quest For Differential Diagnosis Progression and ...mentioning
confidence: 99%
“…Tryptophan (Trp) , an essential amino acid, serve as a precursor for various biochemical reactions in the human body, including the synthesis of serotonin, glycools, glucocorticoids and diabetic drugs [26]. Trp metabolism is closely associated with various cardiovascular diseases , with increasing research examining its relationship with Heart Failure(HF) [27][28][29].…”
Section: Tryptophan Metabolismmentioning
confidence: 99%